Hubungan manajemen waktu terpadu melalui kesiapsiagaan penanganan kegawatdaruratan dengan keselamatan keluarga saat bencana banjir - Azis, Jhon; Zainaro, M Arifki; Hermawan, Dessy (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Floods pose a significant threat to family safety. Integrated time management plays a crucial role in improving family preparedness. Education on effective time management in emergency situations is expected to improve family preparedness and safety. Purpose: To analyze the relationship between integrated time management and family safety in the face of flood disasters. Method: This quantitative study used a quasi-experimental design to measure family knowledge and skills before and after the educational intervention. The research instrument was a questionnaire adapted from the National Disaster Preparedness Guidebook (BNPB). The study population consisted of 277 individuals, with a sample size of 30 individuals aged 17 years and older living along the Kaliawi River. Results: A paired-sample t-test showed a significant difference between pre-test (22.73) and post-test (37.47) scores with a p-value of 0.000 (<0.05). Conclusion: Integrated time management is significantly associated with family safety during flood disasters. Education is effective in improving preparedness and reducing disaster risk. Keywords: Disaster Preparedness; Family Safety; Flood; Integrated Time Management. Pendahuluan: Bencana banjir merupakan ancaman yang cukup besar terhadap keselamatan keluarga. Manajemen waktu yang terpadu memegang peranan penting dalam meningkatkan kesiapsiagaan keluarga. Pendidikan mengenai manajemen waktu yang efektif dalam situasi darurat diharapkan dapat meningkatkan kesiapsiagaan dan keselamatan keluarga. Tujuan: Untuk menganalisis hubungan antara manajemen waktu terpadu dengan keselamatan keluarga dalam menghadapi bencana banjir. Metode: Penelitian kuantitatif menggunakan desain quasi eksperimen untuk mengukur pengetahuan dan keterampilan keluarga sebelum dan sesudah intervensi pendidikan. Instrumen penelitian berupa kuesioner yang diadaptasi dari buku panduan kesiapsiagaan bencana BNPB. Populasi penelitian berjumlah 277 orang dengan sampel sebanyak 30 orang yang berusia ≥17 tahun yang tinggal di sepanjang Sungai Kaliawi. Hasil: Uji t sampel berpasangan menunjukkan perbedaan signifikan antara skor pra-tes (22.73) dan pasca-tes (37.47) dengan nilai p sebesar 0.000 (<0.05). Simpulan: Manajemen waktu terpadu berhubungan signifikan dengan keselamatan keluarga selama bencana banjir. Pendidikan efektif dalam meningkatkan kesiapsiagaan dan mengurangi risiko bencana. Kata Kunci: Banjir; Keselamatan Keluarga; Kesiapsiagaan Bencana; Manajemen Waktu Terintegrasi.